Some legal aspects of personal data protection in the world—experience for Vietnam - Tố Trang Lâm (Cogent Social Sciences, 2024)
The Fourth Industrial Revolution has been taking place strongly on a global scale, besides the positive side, the explosion of technological achievements has raised many issues related to individuals’ rights to their data. In Vietnam, in order to concrete the 2013 Constitution on recognizing, respecting, ensuring human rights, basic rights and personal data protection of citizens, in 17 April 2023, the Vietnamese Government has issued the Decree 13/2023/ND-CP on personal data protection. Because of the relationship between the right to privacy and personal data, this article provides an overview of right to privacy in the international and Vietnamese legal documents, then presents an overview of personal information and personal data in Vietnamese legal documents and at the same time introduces the concept of personal data in Vietnam. In addition, this article also presents some current legal models in the world on personal data protection and the choice of Vietnam. Based on a comparison of regulations in European Union and Asian countries, including Poland, the United Kingdom, Korea, and Japan, on personal data protection agencies, this article proposes the principle of independence in performing the functions, tasks, and powers of personal protection agencies in Vietnam today.